BELALANG SEMBAH DALAM HIASAN DINDING TEKNIK BATIK DAN SULAMAN - Fisanika Praba Ningrum, Drs. Erwin A, M.Sn., Dra. Minarsih, M.Sn. (Universitas Negeri Padang, 2017)
The aim is to create a wall decoration craft objects praying mantis through batik and embroidery techniques. The work is titled ruler, energetic, graceful, wise, vigilant, resolute, and tranquility. The title is taken from human nature, the author connects with human locusts as this final simbol.Karya through five stages, namely preparation phase (exploration), phase zoning ideas (elaboration), synthesis, concept and realization stages of completion. This work is done manually, resulting in a unique piece of art and has a value that can be used to embellish ruangan. My it happen ideas and techniques can be developed by the author or other authors in the future.